Digital payments and bank competition - Verdier, Marianne (Journal of Financial Stability, 2024)
This article examines how competition between banks and a digital PSP impacts the lending rate and the consumers’ use of payment instruments. The digital PSP offers a digital wallet and payment services, but does not offer credit. In contrast, banks invest their deposits in lending activities, which implies that they may incur some costs of adjusting their liquidity needs when consumers make payments. I show that the adoption of the digital wallet for payments may sometimes increase the volume of payments by bank deposit transfers and the lending rate. This results from banks’ trade-off between lowering their costs of liquidity when consumers pay from their digital wallet and reducing the revenues they receive from bank transfer fees.